Analisis Interpretasi Pajak Dan Implikasinya Menurut Perspektif Wajib Pajak Orang Pribadi di Fakultas Ekonomi Dan Bisnis Universitas Muslim Nusantara Al-Washliyah Medan - Jayusman, Sri Fitria; Munawaroh; Dewi, Ratna Sari; Hidayat, Toni; Siregar, Horia; Munawaroh, Wilda Sri (JURNAL MUTIARA AKUNTANSI, 2024)
This study seeks to ascertain the perception of Individual Taxpayers on the interpretation of Income Tax, as well as the extent of understanding among Taxpayers at the Faculty of Economics and Business, Al-Washliyah Muslim University, Medan. This study employs descriptive qualitative methodologies, specifically case studies, to gain a comprehensive and in-depth understanding of a specific case. The researcher aims to investigate how Individual Taxpayers at the Faculty of Economics and Business, Al-Washliyah Muslim University Medan interpret taxes and the resulting implications. This research was conducted in the Faculty of Economics and Business, Al-Washliyah Muslim Nusantara University, located in Medan. The number of informants to be interviewed in this research cannot be determined as the sample collection employs a judgment procedure. The data collection methods employed in this research encompass a preliminary survey, a literature review, and field data collection. Qualitative data analysis is conducted through an interactive process that involves data reduction, data presentation, and generating conclusions. The findings of this study indicate that Individual Taxpayers in the Faculty of Economics and Business, Al-Washliyah Muslim Nusantara University, Medan possess a favorable understanding of their responsibility to fulfill their income tax obligations. The comprehension of income tax imposition among individual taxpayers is generally satisfactory, yet there are also persons who express dissent when a portion of their assets is allocated towards tax” payment.